Role of Key Infectivity Parameters in the Transmission of Ebola Virus Makona in Macaques. (9th October 2021) - de La Vega, Marc Antoine; Wong, Gary; Wei, Haiyan; He, Shihua; Bello, Alexander; Fausther-Bovendo, Hugues; Audet, Jonathan; Tierney, Kevin; Tran, Kaylie; Soule, Geoff; Racine, Trina; Strong, James E; et al.
Abstract: Many characteristics associated with Ebola virus disease remain to be fully understood. It is known that direct contact with infected bodily fluids is an associated risk factor, but few studies have investigated parameters associated with transmission between individuals, such as the dose of virus required to facilitate spread and route of infection. Therefore, we sought to characterize the impact by route of infection, viremia, and viral shedding through various mucosae, with regards to intraspecies transmission of Ebola virus in a nonhuman primate model. Here, challenge via the esophagus or aerosol to the face did not result in clinical disease, although seroconversion of both challenged and contact animals was observed in the latter. Subsequent intramuscular or intratracheal challenges suggest that viral loads determine transmission likelihood to naive animals in an intramuscular-challenge model, which is greatly facilitated in an intratracheal-challenge model where transmission from challenged to direct contact animal was observed consistently. Abstract : Challenge of nonhuman primates with the Makona variant of Ebola virus suggests that viral loads as a result of shedding determine transmission likelihood to naive animals in an intramuscular-challenge model, where transmission from challenged to direct contact animal was observed consistently in an intratracheal-challenge model.